Year-end oversight in Local Government: a case study of water and sanitation service delivery at Amathole District Municipality - Seoke, Duncan (Rhodes University, Faculty of Humanities, Department of Sociology)
Poor service delivery is a challenge that has continued to plague the constitutional democracy of South Africa. Legislation has, in response, been passed to ensure efficient service delivery. Despite this legislation, municipal service delivery has been alarmingly poor, and reports on municipal performance and newspaper articles have corroborated this. On the causes of poor service delivery, the existing literature appears to have focused on financial mismanagement, corruption, and the incapacity of officials. Absent from existing literature are discussions on how municipal service delivery is affected by the lack of interrelatedness between municipal public resource management processes (such as revenue collection, expenditure management and oversight). This dissertation addresses this gap by examining the municipal public resource management processes from an oversight perspective. The study sought to analyse the effectiveness of year-end oversight at Amathole District Municipality (ADM) over water and sanitation services. This research aimed to study the year-end oversight over service delivery with reference to the Municipal Public Resource Management (MPRM) model. According to the model, effective service delivery includes inter alia effective oversight, as oversight forms part of the entire system of the municipal resource management cycle. Thus, for the MPRM model, oversight should be exercised on all these processes. The research was a desktop analysis that used both a qualitative and quantitative research methodology. The primary document analysed was the ADM Oversight Report (OR). This report is produced by the Municipal Public Accounts Committee (MPAC) and reflects the year-end oversight conducted by the MPAC on the municipality's activities. In the analysis of the OR, it was concluded that the ADM MPAC had failed to conduct effective year-end oversight of W&S services. The efficacy of the ADM MPAC's year-end oversight was measured against guidelines for effective year-end oversight from the National Treasury and the MPRM model. The findings suggested that there were inefficiencies in the manner that the ADM MPAC exercised its year-end oversight.
Keywords: Municipal services -- South Africa Amathole District Municipality; Municipal reports; Local government -- South Africa Amathole District Municipality; Urban sanitation -- South Africa Amathole District Municipality; Municipal water supply -- South Africa Amathole District Municipality